Detritus Quality and Locality Determines Survival and Mass, but Not Export, of Wood Frogs at Metamorphosis - Milanovich, Joseph R. (PLoS One, 2016)
Single-site experiments have demonstrated detritus quality in wetlands can have strongly negative, neutral, and even positive influences on wildlife. However, an examination of the influence of detritus quality across several regions is lacking and can provide information on whether impacts from variation in detritus quality are consistent across species with wide ranges. To address this gap in regional studies we examined effects of emergent and allochthonous detritus of different nutrient qualities on amphibians and assessed a mechanism that may contribute to potential impacts. We used aquatic mesocosms to raise wood frogs (Rana sylvatica) from two regions of the United States with whole plants from purple loosestrife (Lythrum salicaria), leaf litter from native hardwood trees, and a mixture of both. We examined several metrics of amphibian fitness and life history, including survival, number of days to metamorphosis, and size at metamorphosis. Further, we quantified whether the effects of detritus type could translate to variation in anuran biomass or standing stock of nitrogen or phosphorus export. Our results show detritus with high nutrient quality (purple loosestrife) negatively influenced survival of wood frogs, but increased size of metamorphic individuals in two different regions of the United States. Despite the decrease in survival, the increase in size of post-metamorphic anurans raised with high quality detritus resulted in anuran biomass and standing stock of N and P export being similar across treatments at both locations. These results further demonstrate the role of plant quality in shaping wetland ecosystem dynamics, and represent the first demonstration that effects are consistent within species across ecoregional boundaries.